Implementasi Program Bina Pribadi Islami (BPI) dalam Membentuk Karakter Islami pada Peserta Didik Kelas Sembilan di SMPIT Ibnu Khaldun Lembang - Zirli Fera Zaira Zunaba; Mujahid Rasyid; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. The character of students in this day and age is declining due to globalisation that continues to develop and advance. Therefore, school is one of the places for character education, where students are supervised, guided, and directed, especially Islamic character. SIT has a typical kediniyahan programme, namely the Islamic Personal Development programme. The purpose of this study is to determine the preparation; implementation; evaluation; supporting and inhibiting factors of the Islamic Personal Development programme in shaping Islamic character in grade nine students at SMPIT Ibnu Khaldun Lembang. The approach used is qualitative and descriptive method. The research subjects were the principal, BPI coach, mentor, and grade nine students. Data collection techniques used, namely interviews, observation, and documentation. The results of this study, from the preparation of programme activities which include planning BPI activities, mapping the material, allocating time, allocating the place of activity, designing strategies in instilling character values, and determining the method. Then, in the implementation, starting from the opening, core activities, and closing activities, it involves students in organising and leading BPI activities, as a form of strategy in instilling Islamic character values. In addition, evaluating the worship of amal yaumiyah is one of the mentor's strategies in instilling an attitude of being honest, trustworthy, and responsible. Furthermore, the evaluation is in the form of a typical curriculum report card, and the assessment aspects include knowledge, attendance, attitude, and amal yaumiyah. Based on the evaluation of the BPI programme, that this BPI programme has a good impact starting from worship, knowledge, and of course their Islamic character which has begun to be embedded. The supporting factors are competent human resources, curriculum, school carrying capacity and infrastructure. While the obstacles are the lack of human resources, and the influence of social media. Abstrak. Karakter peserta didik di zaman sekarang ini semakin menurun akibat globalisasi yang terus berkembang dan maju. Oleh karena itu sekolah sebagai salah satu tempat pendidikan karakter, yang dimana peserta didik diawasi, dibimbing, dan diarahkan, terutama karakter Islami. SIT memiliki program khas kediniyahan, yaitu program Bina Pribadi Islami. Adapun tujuan dari penelitian ini adalah Untuk mengetahui persiapan; pelaksanaan; evaluasi; faktor pendukung dan penghambat program Bina Pribadi Islami dalam membentuk karakter Islami pada peserta didik kelas Sembilan di SMPIT Ibnu Khaldun Lembang. Pendekatan yang digunakan adalah kualitatif dan metode desktiptif. Subjek penelitiannya, yaitu kepala sekolah, Pembina BPI, mentor, dan peserta didik kelas Sembilan. Teknik pengumpulan data yang digunakan, yakni wawancara, observasi, dan dokumentasi. Hasil dari penelitian ini, dari persiapan kegiatan program yang meliputi perencanaan kegiatan BPI, pemetaan materi, pengalokasian waktu, pengalokasian tempat kegiatan, merancang startegi dalam menanamkan nilai-nilai karakter, serta menentukan metodenya. Kemudian, dalam pelaksanaanna dimulai dari pembukaan, kegiatan inti, dan kegiatan penutup melibatkan peserta didik dalam mengatur dan memimpin kegiatan BPI, sebagai bentuk stategi dalam menanamkan nilai-nilai karakter Islami. Selain itu, pengevaluasian ibadah amal yaumiyah merupakan salah satu stategi mentor dalam menanamkan sikap bersikap jujur, amanah, dan tanggung jawab. Selanjutnya, pengevaluasiannya dalam bentuk rapor kurikulum khas, dan aspek penilaiannya mencakup pengetahuan, kehadiran, sikap, dan amal yaumiyah. Berdasarkan pengevaluasian program BPI, bahwa program BPI ini membawa dampak yang baik mulai dari ibadah, ilmunya, dan tentunya karakter Islami mereka yang sudah mulai tertanam. Faktor pendukungnya yakni SDM yang kompeten, kurikulum, daya dukung sekolah dan sarana prasarana. Sedangkan penghambatnya adalah jumlah SDM yang kurang, dan pengaruh sosial media.